Commercial fisheries interactions with oil and gas pipelines in the North Sea: considerations for decommissioning. (15th July 2017) - Rouse, Sally; Kafas, Andronikos; Catarino, Rui; Peter, Hayes
Abstract: Commercial fisheries and oil and gas extraction are both spatially extensive industries in the North Sea (NS), and inevitably there is physical interaction where the two activities coincide. Regular contact between fishing gear and pipelines may risk pipeline integrity and could lead to gear snagging. It is also known, anecdotally, that some vessels target pipelines, potentially benefiting from local artificial reef effects. The impacts of pipeline decommissioning options (removal vs. in situ ) on commercial fisheries must be evaluated as part of the consenting process, but the degree of interaction between the two is presently unknown in the NS. Vessel Monitoring System (VMS) data for the Scottish demersal fleet were analysed with spatial data on pipelines. Approximately one-third (36.1%) of trips fished within 200 m of a pipeline over a 5-year period, suggesting that pipelines are subjected to regular interaction with fishing gear. The fishing effort (in hours) associated with pipelines was 2.52% of the total effort, compared to 1.33% in an equivalent area of seabed 1 km away, implying modest aggregation of fishing around pipelines. Only a small percentage (0.93%) of fishing trips actively targeted pipelines as fishing grounds. The highest level of fishing around pipelines occurred in the northeast NS. Pipeline sections with >100 h of fishing were typically larger diameter pipelines. The results suggest that pipeline decommissioning may have both negative (displacement of aggregated effort) and positive (reduced snagging potential) outcomes for commercial fisheries. It is recommended that where there is little or no fishing activity associated with pipelines, receptors other than fishing should be prioritized when selecting decommissioning strategies. Additionally, the intensity of fishing around pipelines should be used to inform the frequency of post-decommissioning integrity monitoring for any pipelines left in situ.